2008
DOI: 10.1890/07-0556.1
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Free‐tailed Bats as Insect Pest Regulators in Transgenic and Conventional Cotton Crops

Abstract: Abstract. During the past 12 000 years agricultural systems have transitioned from natural habitats to conventional agricultural regions and recently to large areas of genetically engineered (GE) croplands. This GE revolution occurred for cotton in a span of slightly more than a decade during which a switch occurred in major cotton production areas from growing 100% conventional cotton to an environment in which 95% transgenics are grown. Ecological interactions between GE targeted insects and other insectivor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 19 publications
3
96
1
1
Order By: Relevance
“…The metaanalysis of Van Bael et al (9), which was based upon a subset of the data presented here (n = 48 studies), found parallel results for bird effects on predaceous and herbivorous arthropods in trees and understory shrubs. Although negative effects of vertebrate insectivores on arthropod predators may arise in part from competition for a shared prey base of herbivores, diet studies clearly demonstrate that vertebrate insectivores also directly consume predatory arthropods (10,19,20). This first result-that vertebrate insectivores act as intraguild predators, suppressing both intermediate predators and herbivores-thus sets the stage for our test of the subsequent predictions.…”
Section: Resultsmentioning
confidence: 92%
“…The metaanalysis of Van Bael et al (9), which was based upon a subset of the data presented here (n = 48 studies), found parallel results for bird effects on predaceous and herbivorous arthropods in trees and understory shrubs. Although negative effects of vertebrate insectivores on arthropod predators may arise in part from competition for a shared prey base of herbivores, diet studies clearly demonstrate that vertebrate insectivores also directly consume predatory arthropods (10,19,20). This first result-that vertebrate insectivores act as intraguild predators, suppressing both intermediate predators and herbivores-thus sets the stage for our test of the subsequent predictions.…”
Section: Resultsmentioning
confidence: 92%
“…The trickle-down impacts on agricultural production could be substantial, although quantitative evidence is lacking. The effects of GM crops incorporating insecticidal traits have been investigated largely in the context of the provisioning of predation services (Federico et al 2008;Lopez-Hoffman et al 2014; see next section); however, declines in pest numbers associated with the use of these crops could result in population declines of insectivorous bats (LopezHoffman et al 2014). …”
Section: Pesticide Impacts On Bat Populationsmentioning
confidence: 99%
“…Extending these estimates to agricultural areas throughout the USA suggests that bat predation could have a value of nearly US $23 billion annually (Boyles et al 2011). These benefits hold for both conventional and transgenic cotton (Federico et al 2008), although the introduction of Bt cotton (a genetically modified organism whose tissues produce an insecticide derived from the bacterium Bacillus thuringiensis), coupled with reduced area in cotton cultivation, has led to a decline in the overall value of this pest limitation service (Lopez-Hoffman et al 2014). …”
Section: Insectivorous Bats and Pest Limitationmentioning
confidence: 99%
“…Our study roost, which consisted of more than 1000 individuals every year, is located in a small patch of forest, which is surrounded by extensive agricultural fields. If this species uses these agricultural fields as a feeding habitat, their ecological function in the agricultural ecosystem might be as influential as has been shown for other insectivorous bat species (Cleveland et al 2006;Federico et al 2008;Williams-Guillén et al 2008). In this case the conservation and management of V. sinensis in the study area is important for economic reasons.…”
Section: Discussionmentioning
confidence: 87%